2010
DOI: 10.1186/1742-4690-7-79
|View full text |Cite
|
Sign up to set email alerts
|

GPI-anchored single chain Fv - an effective way to capture transiently-exposed neutralization epitopes on HIV-1 envelope spike

Abstract: BackgroundIdentification of broad neutralization epitopes in HIV-1 envelope spikes is paramount for HIV-1 vaccine development. A few broad neutralization epitopes identified so far are present on the surface of native HIV-1 envelope spikes whose recognition by antibodies does not depend on conformational changes of the envelope spikes. However, HIV-1 envelope spikes also contain transiently-exposed neutralization epitopes, which are more difficult to identify.ResultsIn this study, we constructed single chain F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(76 citation statements)
references
References 74 publications
3
71
2
Order By: Relevance
“…It is likely that after gp120-CD4 binding, the available space is not sufficient to accommodate large molecules. Despite the broad range of neutralization activities of X5, we and others showed that free scFv X5 had a relatively lower level of inhibition of virus entry (37,49). X5 function is great enhanced by the addition of soluble CD4.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that after gp120-CD4 binding, the available space is not sufficient to accommodate large molecules. Despite the broad range of neutralization activities of X5, we and others showed that free scFv X5 had a relatively lower level of inhibition of virus entry (37,49). X5 function is great enhanced by the addition of soluble CD4.…”
Section: Discussionmentioning
confidence: 99%
“…To generate stable S2 clones, a limiting dilution assay was performed as described earlier (54). Briefly, 1.5 ϫ 10 2 S2 transfectants were mixed with 10 6 parental S2 cells (feeder layer cells) in 10 ml of Drosophila Schneider 2 medium supplemented with 10% FBS, 100 U of penicillin/ml, 100 U of streptomycin/ml, and 100 mg of L-glutamine/liter.…”
Section: Methodsmentioning
confidence: 99%
“…TZM-bl cells were obtained from the NIH AIDS Research and Reference Reagent Program (ARRRP; Germantown, MD) (9,38). The human CD4 ϩ T cell line CEMss-CCR5 was generated as described previously (54). These cells were maintained in complete DMEM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous Abs were described for their binding to the CD4-induced site and the most interesting by their breadth neutralizing capacities are the 17b, X5, m18, and m14 which all contains long H3s playing a major role in their mechanism of binding (table 1). The H3s region of X5, m6 and m9 appear to be very flexible and highly potent to neutralize the virus (Wen et al, 2010;Zhu et al, 2006) …”
Section: Cd4-induced Regionmentioning
confidence: 99%